2017
DOI: 10.1371/journal.pone.0181565
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis on herpes zoster and the risk of cardiac and cerebrovascular events

Abstract: BackgroundPatients who develop herpes zoster or herpes zoster ophthalmicus may be at risk for cerebrovascular and cardiac complications. We systematically reviewed the published literature to determine the association between herpes zoster and its subtypes with the occurrence of cerebrovascular and cardiac events.Methods/ResultsSystematic searches of PubMed (MEDLINE), SCOPUS (Embase) and Google Scholar were performed in December 2016. Eligible studies were cohort, case-control, and self-controlled case-series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 50 publications
(117 reference statements)
0
57
0
1
Order By: Relevance
“…Also, in immunocompromised patients having VZV infection: atypical skin eruption may be encountered and disseminated infection may occur in the absence of skin lesions [48,50]. Constitutional symptoms and prodromal manifestations such as fever, malaise and local pain usually occur and they are followed by the typical skin eruptions of both chickenpox and herpes zoster [44,47,49,51]. VZV infections may be complicated by: secondary bacterial infection, pneumonia, post-herpetic neuralgia, stroke and other vasculopathies, meningoencephalitis, segmental weakness and myelopathy, cranial neuropathies, giant cell arteritis, Guillain-Barre syndrome, enteric complications, severe local infection such as Ramsay Hunt syndrome, visceral and disseminated involvement, and death particularly in immunocompromised patients and complicated cases [44,47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in immunocompromised patients having VZV infection: atypical skin eruption may be encountered and disseminated infection may occur in the absence of skin lesions [48,50]. Constitutional symptoms and prodromal manifestations such as fever, malaise and local pain usually occur and they are followed by the typical skin eruptions of both chickenpox and herpes zoster [44,47,49,51]. VZV infections may be complicated by: secondary bacterial infection, pneumonia, post-herpetic neuralgia, stroke and other vasculopathies, meningoencephalitis, segmental weakness and myelopathy, cranial neuropathies, giant cell arteritis, Guillain-Barre syndrome, enteric complications, severe local infection such as Ramsay Hunt syndrome, visceral and disseminated involvement, and death particularly in immunocompromised patients and complicated cases [44,47,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…5 Recent meta-analyses have convincingly demonstrated an increased risk of cerebrovascular events after HZO, reported variably as both a relative risk of 1.9 6 and as an odds ratio of 4.42. 7 Subgroup analyses from both of these cohorts demonstrate increased risk of isolated ischemic stroke in addition to nonspecific cerebrovascular disease but do not clearly demonstrate increased risk of hemorrhagic stroke alone. While the greatest risk occurs 1 month following diagnosis, 6 risk of stroke is elevated for up to 1 year.…”
Section: Varicella Zoster Virusmentioning
confidence: 98%
“…It is estimated that reactivation of latent herpes zoster infections may increase the risk of stroke by as much as 50% in the month immediately after reactivation, with the elevated risk potentially persisting for months [10]. A meta-analysis of published studies suggested that reactivation of herpes zoster increases the risk of a cerebrovascular or cardiovascular event by 20-40% and 10-30%, respectively, in the year after onset [29,30], and that vaccination may approximately halve this risk in adults aged 65-69 years [31]. The consistent temporal association of zoster and an elevated risk of developing cardiac or cerebrovascular disease, together with the observation that anti-viral therapy or vaccination appear to diminish risk, argue strongly for a causal effect [30].…”
Section: Vaccination As a Tool For Maintaining Wellnessmentioning
confidence: 99%